Evaluating the Association Between Genetically Proxied Neurodevelopmental Language Phenotypes and the Risk of Primary Progressive Aphasia. (2nd May 2023) - Nassan, Malik; Piras, Ignazio S.; Rogalski, Emily; Geula, Changiz; Mesulam, M. Marsel; Huentelman, Matt
Abstract : Background and Objectives: Primary progressive aphasia (PPA) is a neurodegenerative syndrome of progressive language decline. PPA has 3 main subtypes: logopenic, semantic, and agrammatic. Observational studies suggested an association between language-related neurodevelopmental phenotypes and an increased risk of PPA. We sought to assess such relationships through Mendelian randomization (MR) approach, which can suggest potentially causal associations. Methods: Genome-wide significant single-nucleotide polymorphisms (SNPs) associated with dyslexia (42 SNPs), developmental speech disorders (29 SNPs), and left-handedness (41 SNPs) were used as genetic proxies for the exposures. Eighteen of 41 SNPs of left-handedness were associated with structural asymmetry of the cerebral cortex. Genome-wide association study summary statistics were obtained from publicly available databases for semantic (308 cases/616 controls) and agrammatic PPA (269 cases/538 controls). The logopenic PPA (324 cases/3, 444 controls) was approximated by proxy through the rubric of clinically diagnosed Alzheimer disease with salient language impairment. Inverse-weighted variance MR was performed as the main analysis for testing the relationship between the exposures and outcomes. Sensitivity analyses were completed to test the robustness of the results. Results: Dyslexia, developmental speech disorders, and left-handedness were not associated with any PPA subtype ( p > 0.05). The genetic proxy of cortical asymmetry in left-handedness was significantly associated with agrammatic PPA (β = 4.3, p = 0.007), but not with other PPA subtypes. This association was driven by microtubule-related genes, primarily by a variant that is in complete linkage disequilibrium with MAPT gene. Sensitivity analyses were overall consistent with the primary analyses. Discussion: Our results do not support a causal association between dyslexia, developmental speech disorders, and handedness with any of the PPA subtypes. Our data suggest a complex association between cortical asymmetry genes and agrammatic PPA. Whether the additional association with left-handedness is necessary remains to be determined but is unlikely, given the absence of association between left-handedness and PPA. Genetic proxy of brain asymmetry (regardless of handedness) was not tested as an exposure due to lack of suitable genetic proxy. Furthermore, the genes related to cortical asymmetry associated with agrammatic PPA are implicated in microtubule-related proteins ( TUBA1B, TUBB, and MAPT ), which is keeping with the association of tau-related neurodegeneration in this PPA variant.